Iron‐induced oxidative rat liver injury after non–heart‐beating warm ischemia is mediated by tumor necrosis factor α and prevented by deferoxamine. Issue 8 (3rd July 2014) - Niu, Xianwa; Huang, Wen Hua; De Boer, Bastiaan; Delriviere, Luc; Mou, Ling Jun; Jeffrey, Gary P.
<x xml:space="preserve">Abstract</x> This study investigated iron‐induced injury after warm ischemia in a non–heart‐beating (NHB) rat liver model and the effects of deferoxamine (DFO). Livers from heart‐beating (HB) rats or rats that were NHB for 60 minutes were stored in University of Wisconsin solution for 5 hours at 4°C [cold storage (CS)] and then were subjected to 2 hours of machine reperfusion (MRP) at 37°C. Three NHB groups were compared: (1) no DFO, (2) DFO 30 minutes before cardiac arrest and during CS and MRP, and (3) DFO during CS and MRP. Aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) levels in the NHB perfusate were significantly elevated (P < 0.01) in comparison with levels in HB controls after CS and MRP. After CS, the levels of iron and tumor necrosis factor α (TNF‐α) were 0.077 ± 0.007 μmol/g and 151 ± 26 pg/g, respectively, in the NHB group and 0.022 ± 0.004 μmol/g and 17 ± 7 pg/g, respectively, in the HB group (P < 0.01). After MRP, LDH significantly correlated with iron (R2 = 0.81, P < 0.01). The DFO pretreatment of NHB donors decreased AST (7.3 ± 0.8 versus 4.0 ± 0.5 U/g of liver, P < 0.05) and LDH (42.5 ± 4.1 versus 20.4 ± 2.5 U/g of liver, P < 0.05) with 2 hours of MRP and increased bile flow during MRP (142 ± 34 versus 240 ± 18 μL/g, P < 0.05). It also reduced the levels of iron (0.077 ± 0.007 versus 0.050 ± 0.008 μmol/g, P < 0.05) and TNF‐α (151 ± 26 versus 51 ± 13 pg/g, P < 0.05) after CS and the levels of lipid peroxidation products F2‐isoprostane (149 ± 11 versus 99 ± 10 ng/g, P < 0.05) and malondialdehyde (1.58 ± 0.1 versus 1.14 ± 0.08 μmol/g, P < 0.05) after MRP. In conclusion, iron‐initiated oxidative stress is likely involved in NHB donor liver injury, and importantly, DFO pretreatment reduces liver damage. Liver Transpl 20:904–911, 2014. © 2014 AASLD.